Professional caregivers' knowledge, beliefs and attitudes about awareness in advanced dementia: a systematic review of qualitative studies. (21st February 2019) - Rice, H.; Howard, R.; Huntley, J.
ABSTRACT: Objectives: Awareness can be defined as a response to, or evaluation of, an aspect of one's situation or internal state. Awareness becomes impaired as dementia progresses; however, the exact nature and degree of impairment in advanced dementia remains unclear. The extent to which caregivers understand or make assumptions about the level and nature of awareness in advanced dementia may have a significant impact on their ability to appropriately respond to and care for the person with dementia. This systematic review examines the literature regarding professional caregiver perceptions about awareness in advanced dementia. Design: A systematic search of online literature databases (PsychInfo, Medline, Embase, CINAHL) was conducted up to January 15, 2018, using a range of search terms related to dementia, awareness and caregiver attitudes. Results: The systematic review included a total of 10 qualitative studies that were heterogeneous in aspects of design, including analyses. Narrative synthesis was used to integrate results. Four major themes were identified from review of the papers: how professional caregivers defined awareness; professional caregiver beliefs about what influences the expression of awareness; professional caregiver beliefs around how to assess awareness in advanced dementia; and the perceived impact of episodes of increased awareness on the person with dementia and caregiver. Sub-themes were identified within each of these areas. Conclusion: This review highlights the importance of professional caregiver perceptions of awareness in advanced dementia. Supporting professional caregivers to assess and understand the nature of awareness in advanced dementia would improve their approach to care and outcomes for people with dementia.